Social Support, Sense of Belonging, and Communication Technology Use Among Paid and Unpaid Caregivers of Middle-Aged and Older Adults - Lee, Shinduk; Ory, Marcia G.; Dahlke, Deborah Vollmer; Smith, Matthew Lee (Frontiers in Public Health, 2022)
Objectives: The objectives of this study are to: (1) describe communication technology use among middle-aged and older caregivers of middle-aged and older adults in a natural (non-experimental) setting; and (2) examine the association between communication technology use, perceived social support, and sense of belonging among caregivers of middle-aged and older adults. Methods: Means and standard deviations, or frequencies and percentages, were used to describe study participants. Chi-square tests or independent sample t-tests were used to compare sociodemographic characteristics, communication technology use, perceived social support, and sense of belonging to the local community between paid and unpaid caregivers. Multivariable regression analysis was performed to predict each outcome (i.e., sense of belonging and social support) based on the use of texting or communication applications. Results: The average age of participants was age 64.2 years, and the majority was female (74.8%) and non-Hispanic White (66.9%). Compared to paid caregivers, unpaid caregivers were older (64.5 vs. 62.2 years, p=.022) and a larger proportion were non-Hispanic White (70.8% vs. 47.7%, p<.001). Nearly 83% of the study participants reported using texting or communication applications (81.5% among paid caregivers and 83.1% among unpaid caregivers, p=.718). After adjusting for caregivers’ age, sex, race/ethnicity, and education, a significantly higher sense of belonging was observed among paid caregivers than unpaid caregivers (b=9.40, p=.009). After adjusting for caregivers’ age, sex, race/ethnicity, and education, the use of texting or other communication applications significantly increased caregivers’ perceived availability of social support (b=0.35, p=001). Conclusions: These study results showed a greater sense of belonging to the local community among paid caregivers compared to unpaid caregivers. The use of communication technology was associated with an increased sense of belonging to their local community among paid caregivers, yet the use of communication technology did not contribute to feelings of belonging among unpaid caregivers. In an aging society, both paid and unpaid caregivers are essential elements of the care system. Research is needed to understand the social support needs of paid and unpaid caregivers and the types of interventions to promote social support and community engagement for both groups.